The COVID-19 Pandemic and Emerging Cultural Assets. Issue 4 (2nd October 2022) - Borrero, Noah; Yeh, Christine J.; Dela Cruz, Gabriel; Collins, Teresa
ABSTRACT: In an attempt to name challenges and envision possibilities facing educators during the COVID-19 pandemic, this article asks, what are examples of culturally relevant pedagogy emergent from forced distance-learning that promote and foster students' cultural assets? The authors present a model for identifying cultural assets and reflect upon and share three examples from their teaching at the onset of the pandemic: (1) The Corona Chronicles, a showcase of personal editorials created by fourth graders, (2) QuaranTeen, a podcast created by eleventh graders to explore and learn from one another amidst distance learning, and (3) Ecological Asset-Mapping, a pedagogical tool for pre-service teachers to reflect upon their own—and learn from their K-12 students'—cultural assets. These pedagogical examples are portrayed and discussed in ways to foster student, family, and community cultural assets as foundations of meaningful learning.